Metabolic Syndrome Components and Nutritional Status among Hypertensive Outpatiens at Dr. Hasan Sadikin General Hospital Bandung - Lira Mirandus; Hikmat Permana; Siti Nur Fatimah (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: Metabolic syndrome and overnutritional status (overweight and obesity) are examples of determinants that can give rise to hypertension, so the three diseases are correlated with each other. This study aimed to reveal metabolic syndrome components and nutritional status among hypertensive outpatients.Methods: This study involved 44 hypertensive outpatients who visited the Nephrology and Hypertension Clinic of Dr. Hasan Sadikin Hospital, Bandung in September to October 2013. Anthropometric and blood pressure measurements, anamnesis, and medical record data collection were carried out to describe the patient’s metabolic syndrome components by using International Diabetes Federation criteria on South Asian people and nutritional status by WHO classification in Asian people.Results: Among respondents, 25 (57%) had abdominal obesity, 14 (32%) had hypertrygliceridemias, 14 (32%) had low HDL cholestrol, 19 (43%) were taking lipid-lowering medications, 20 (45 %) had high level of fasting blood glucose, 21 (48%) had been diagnosed as mellitus type 2, 15 (34%) had high blood pressure, 40 (91%) were taking antihypertensive medications, 19 (43%) had metabolic syndrome, and 31 (70%) were overweight or obese.Conclusions: Less than a half of the respondents meet the metabolic syndrome criteria and over two third of them are at overnutrition state (overweight or obesity). [AMJ.2016;3(3):476–80]DOI: 10.15850/amj.v3n3.862